2020
DOI: 10.3390/vaccines8010060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Clinical and Economic Impact of Different Immunization Protocols of Measles, Mumps, Rubella and Varicella in Internationally Adopted Children

Abstract: The appropriate immunization of internationally adopted children (IAC) is currently under debate and different approaches have been suggested. The aim of this study is to evaluate the clinical and economic impact of different strategies of measles, mumps, rubella, and varicella (MMRV) immunization in IAC in Italy. A decision analysis model was developed to compare three strategies: presumptive immunization, pre-vaccination serotesting and vaccination based on documentation of previous immunization. Main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…One provided a formula for determining the choice [ 34 ]. Another showed an incremental cost of £394 per case prevented with testing [ 32 ]. A third reported an incremental cost per QALY gained of £10,816 for presumptive vaccination against testing and vaccinating susceptibles [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One provided a formula for determining the choice [ 34 ]. Another showed an incremental cost of £394 per case prevented with testing [ 32 ]. A third reported an incremental cost per QALY gained of £10,816 for presumptive vaccination against testing and vaccinating susceptibles [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies tended to be the most recently published, with an average publication date of 2015. 26 ; susceptible children adopted from abroad 1-18 years old 32 One dose 26 , two doses 32 All newly arriving asylum seekers age 15−39 33 Vaccination of all susceptible in response to outbreak. Two doses vs usual response 33 Switzerland Cost per person 167% higher 33 n/a Primigravidae born in UK or Bangladesh 37 Two doses vs no vaccination UK Verbal screening followed by serotesting may be cost-saving to the NHS for both UK-and Bangladesh-born primigravidae 37 n/a Susceptible schoolchildren 6-12 and adolescents 13−17 25 ; 20 year olds and older 28 ; susceptible children eligible for kidney transplant 30 ; recently arrived refugees 1 to 20 years of age 34 ; women 15-49 postpartum 36 ; women postpartum 38 One dose vs no vaccination 25 ; two doses vs no vaccination 28 ; Pretreatment vaccination two doses vs usual care 30 ; One dose under 13, two doses 13 and over vs no vaccination 34 ; two doses vs no vaccination 36…”
Section: Results By Type Of Vaccination Programme By Type Of Outcome ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among IAC with an unknown protective status against MMRV, as reported by Boccalini et al, a vaccination strategy based on serotesting results was the most advantageous approach, economically and clinically [ 19 ]. Moreover, another multicenter study conducted ina Northern (Liguria) and a Southern (Apulia) Italian region found poor knowledge but good attitudes among undergraduates about HPV vaccination [ 20 ].…”
Section: Manuscripts Included In the Special Issuementioning
confidence: 99%
“…Furthermore, Boccalini et al economically analyzed the appropriate vaccinations for internationally adopted children in Italy. They concluded that antibody testing was more efficacious [ 12 ]. Meanwhile, Asli et al concluded in the study of health care workers and students in Turkey that it is better to get the rubella vaccine without the screening tests [ 13 ].…”
Section: Introductionmentioning
confidence: 99%